VALUATION OF ACTUARIAL LIABILITY USING MARKOV CHAIN - HIKMAH (NIM : 20813015); Pembimbing : Dr. Udjianna Sekteria Pasaribu, YULIAL
In retirement planning, normal retirement benefits as the main benefit and usually also contain additional benefits are paid when the participants experience disability before retirement, death before or after retirement. The possibility of that situation makes more and more that need to be calculated by the Pension Fund. Therefore, it is required a calculation model that can describe all of that possibilities. A Retirement planning is a term life insurance contract with the normal costs as premiums and the actuarial liabilities as reserves in the pension fund. In this study, will be developed a calculation of prospective actuarial liability using a calculation of life insurance reserves through Markov chain. The calculation of actuarial liability is only for an individu with the same age and situation. It is also required the rates and transition probabilities. The amount of benefits in retirement planning usually depend on the event time so that also required the equation model for these benefits. Moreover, the pension fund can calculate the actuarial liability of participants with a disability pension condition. In this study, the calculation of actuarial liabilitiy using two conditions, namely a defined costs and defined benefit. In the calculation of actuarial liability with the defined costs, pension fund requires initial funding. Furthermore, the rate of increasing in actuarial liability with the defined benefits will be greater than the defined costs. Thus, the results of this calculation can contribute the Pension Fund in determining the company policies.